2001
DOI: 10.1097/00000542-200105000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngolaryngeal Morbidity with the Laryngeal Mask Airway in Spontaneously Breathing Patients

Abstract: Selection of a small laryngeal mask airway (size 4) in spontaneously breathing male patients may be more appropriate to limit the occurrence of sore throat on the first postoperative day. All patients had a fourfold increased risk of developing sore throat when a large LMA was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 19 publications
6
54
0
Order By: Relevance
“…Selection of an appropriately sized device is important for safety and for securing an effective airway. Many studies have been conducted to determine the optimal sizes for the Classic TM LMA 15,16 and the PLMA. [8][9][10] Grady et al 15 suggested that a small LMA (size 4) decreases the incidence of sore throat in spontaneously breathing male patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of an appropriately sized device is important for safety and for securing an effective airway. Many studies have been conducted to determine the optimal sizes for the Classic TM LMA 15,16 and the PLMA. [8][9][10] Grady et al 15 suggested that a small LMA (size 4) decreases the incidence of sore throat in spontaneously breathing male patients.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that a large LMA increased the risk of sore throat fourfold. 15 However, many investigators recommend routine use of a large size for general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…LMA-induced pharyngolaryngeal complications (POST, hoarseness, dysphagia) are related to the insertion technique, number of insertion attempts, LMA size, duration of anaesthesia and surgical position (11,(14)(15)(16). Studies have shown that the use of lubricants to facilitate insertion and cuff pressure control does not reduce the incidence of sore throat (2).…”
Section: Turk J Anaesth Reanim 2014; 42: 123-7mentioning
confidence: 99%
“…Devices with an inflatable cuff have the potential to cause tissue distortion, venous compression, and nerve injury, which explains the increased incidence of associated postoperative morbidity [4] Trauma on insertion, multiple insertions, and pressure exerted by cuff against the pharyngeal mucosa, [21,22] cuff volumes [23] and pressure [24] have all been incriminated for postoperative complications.…”
Section: Discussionmentioning
confidence: 99%